2017
DOI: 10.1111/crj.12716
|View full text |Cite
|
Sign up to set email alerts
|

CPAP and EPAP elicit similar lung deflation in a non‐equivalent mode in GOLD 3‐4 COPD patients

Abstract: Twenty-one eligible COPD patients were studied (13 male/8 female, FEV % predicted of 36.5 ± 9.8). Both CPAP and EPAP demonstrated significant post-pre (Δ) changes for IC and PImax, with mean ΔIC for CPAP and EPAP of 200 ± 100 mL and 170 ± 105 mL (P = .001 for both) in 13 and 12 patients (responders) respectively. There were similar changes in % predicted IC and PImax (∼7%, P = .001 for both) for responders and poor responder/non-responder agreement depending on CPAP/EPAP mode (Kappa = .113, P = .604). There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…The effects of EPAP on HRV complexity during rest in COPD patients are unprecedented and cannot be compared to other scientific studies. One of the main findings of our study with 5 cmH 2 O EPAP was the increase of SpO 2 , different from Müller et al ( 12 ) study, in which they applied 10 cmH 2 O EPAP and found no improvement in SpO 2 . The main effect of the EPAP device consists in increasing expiratory flow and decreasing pulmonary hyperinflation ( 11 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The effects of EPAP on HRV complexity during rest in COPD patients are unprecedented and cannot be compared to other scientific studies. One of the main findings of our study with 5 cmH 2 O EPAP was the increase of SpO 2 , different from Müller et al ( 12 ) study, in which they applied 10 cmH 2 O EPAP and found no improvement in SpO 2 . The main effect of the EPAP device consists in increasing expiratory flow and decreasing pulmonary hyperinflation ( 11 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The main effect of the EPAP device consists in increasing expiratory flow and decreasing pulmonary hyperinflation ( 11 ). EPAP demonstrated equivalent effects to CPAP on static hyperinflation, improvements in inspiratory muscle strength, and inspiratory capacity ( 12 ). The device has been used in COPD patients to assist elimination of pulmonary secretions and induce a reduction in minute ventilation, respiratory rate, and physiological dead space ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation